Basbas: A short feature film about religious fanaticism - Corpuz, Sophia Gale M. (Animo Repository, 2023)
Basbas is a 17-minute short satire film that revolves around the religious themes of faith healing and blind following. It tells the story of Eva and Carlo, a mother and son, resorting to religious healing as their last hope in curing the mother’s terminal disease where they both experience a transformation in their life.The thesis film centers on fanaticism and blind faith, with religion as its primary front. The thesis film discusses Filipino idolatry and blind faith in abusive cult-like religious sects in the country. In several scenes in the film, it exposes the satirical nature of cult conversion where clear actions of malalignment are often misinterpreted into acts of good due to the inherent desperation of soon-to-be converted followers who are preyed upon by the leaders of these sects. Therefore, the film uses religion to create a story about how victims are exploited by preying on their vulnerabilities brought about by socio-economic conditions. Hence, the film explores how religion can be used as a tool for personal gain through weaponizing blind following, with the use of modern methods towards propagating their ideologies. Lastly, Basbas also depicts how people can become slaves to their own desires and have misconceptions about their religion.Due to the nature and sensitivity of the topic of religion, the researchers created a purely fictitious religious organization that does not reflect any existing religion but rather portrays the occurrences and the impact of blind faith and fanaticism that can predispose one’s cognitive ability to criticize reality. 1080p. MP4 Format. Keywords: Fanaticism, Blind Faith, Religious Fanaticism, Religious Consumerism, Goal Directed Behavior, Desire, Intention, and Behavior